2020
DOI: 10.1186/s12969-020-00453-6
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic temporomandibular joint reconstruction in a cohort of adolescent females with juvenile idiopathic arthritis

Abstract: Background: Temporomandibular joint (TMJ) arthritis and involvement is commonly seen in Juvenile Idiopathic Arthritis (JIA). Therapy includes conservative measures, but also includes intraarticular corticosteroid injections (IASI) and systemic immunosuppressive therapy. Despite aggressive medical therapy, some patients develop arthritic changes and frank TMJ ankylosis that can result in persistent pain and limitation in range of motion (ROM). A surgical option is prosthetic TMJ replacement with concurrent corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The titles and abstracts were then screened, and 240 studies did not meet the eligibility criteria and were excluded, resulting in 48 studies included for full-text reading. After full-text reading 15 articles were found with at least 1 report of skeletally immature patients with ankylosis treated with alloplastic TMJR (1,2,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts were then screened, and 240 studies did not meet the eligibility criteria and were excluded, resulting in 48 studies included for full-text reading. After full-text reading 15 articles were found with at least 1 report of skeletally immature patients with ankylosis treated with alloplastic TMJR (1,2,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
“…The suPAR protein was found in 1991 as a marker of cancer progression. Up to these days several studies have shown the association of the protein with chronic diseases, including cardiovascular, renal, hepatic, and pulmonary diseases, and that it's level is an independent predictor of a negative outcome of various infectious diseases, sepsis, and in critically ill patients [30][31][32][33]. As the protein is expressed mainly on immune cells, suPAR reflects the level of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the superiority of alloplastic TMJ TJR in non-rheumatic end-stage joint disease patients has been found to translate to the autoimmune population as well [137]. Outcomes of alloplastic TMJ TJR in RA, PsA, AS, SSc, and JIA patients have been reported, showing consistent improvement in associated pain and dysfunction [138][139][140][141][142][143][144][145][146][147]. The literature nearly unanimously suggests that patients with appropriate indications for TMJ TJR have seen improved, durable outcomes.…”
Section: Total Joint Replacementmentioning
confidence: 99%